A novel polyester composite nanofiltration membrane prepared by interfacial polymerization catalysed by 4-dimethylaminopyridine: Enhanced the water permeability and anti-fouling ability. (26th September 2018) - Cheng, Jun; Zhang, Zhiqiang; Shi, Wenxin; Zhang, Ruijun; Zhang, Bing; Bao, Xian; Guo, Yuan; Cui, Fuyi
Abstract: In this study, 4-dimethylaminopyridine (DMAP) was firstly used as a catalyst in the interfacial polymerization of pentaerythritol (PE) and trimesoyl chloride (TMC) to enhance membrane performance. A series of nanofiltration membranes were prepared using five different DMAP concentrations of 0%, 10%, 20%, 30% and 40% (mass percentage accounting for PE). The filtration test results demonstrated that the water permeability of the typical PE-4 (40% DMAP addition) was 3.47-fold higher than that of the PE-0 (no DMAP addition) with no significant salt rejection loss, indicating that DMAP could effectively improve the water permeability. Characterization by SEM, AFM, and ATR-FTIR indicated that DMAP facilitated the reaction of PE and TMC, which resulted in polyester forming on the surface of the substrate membrane, rather than blocking the membrane pore. Moreover, the PE-DMAP-TMC TFC membrane displayed excellent dye separation performance and high antifouling ability. Graphical abstract: Image 1 Highlights: DMAP was firstly used in the interfacial polymerization of PE and TMC. The water permeability was improved 3.47 folds with no salt rejection loss. The anti-fouling ability was improved by the addition of DMAP.